Integrating exploration as a learning context impacts feelings of empowerment and engagement - Kelly Koller (International Journal of Educational Research Open)
By connecting discoveries in neuroplasticity, neuroevolutionary science, and the role of emotions in learning with a field study, this article investigates the impact of centering exploration as a learning context. Dependent variables in this study, engagement and empowerment, are critically important for learning growth in all types of educational settings. Surveys were conducted in multiple classrooms, across various age groups and content areas, and the impact of students’ feelings of empowerment and engagement was measured after teachers integrated exploration as a theme into a unit of study. Humans have a primal emotion of seeking, which helps us stay motivated through challenges and activates our curiosity. This emotion can potentially be piqued by promoting an outlook of exploration, or an “explorer mindset,” affecting feelings of self-efficacy and the desire to learn. By comparing pre-and post-survey results after an explorer mindset was integrated into a unit, measures of empowerment and engagement that were initially low had risen. Through qualitative data, the study found that students could articulate the concept of an explorer mindset with evident themes of empowerment and engagement. As empowerment and engagement affect academic achievement, the results of this study are important in educational research.